Big SIS is watching you. - Siegele, Ludwig (Economist)
The article presents information on societal information-technology systems (SIS). These are described as specialized computer networks designed to integrate and automate the management of public utilities such as transportation, power plants, and the water supply. Problems which could arise due to cybernetic malfunctions or hacking are noted.